Resveratrol-sulfates provide an intracellular reservoir for generation of parent resveratrol, which induces autophagy in cancer cells - Andreadi, Catherine (Landes Bioscience, 2014)
Resveratrol has many proposed health benefits, including the prevention of cancers, but its low bioavailability is considered a limiting factor in translating these effects to humans. Based on in vivo and clinical studies we have shown that resveratrol is indeed rapidly metabolized by phase II enzymes, and that resveratrol sulfates are deconjugated by steroid sulfatases to afford free resveratrol in vitro and in vivo and hence act as an intracellular reservoir for resveratrol. Further, we have demonstrated that at clinically achievable concentrations of resveratrol sulfate, parent resveratrol is regenerated within human colorectal cancer, but not normal epithelial cells, and is responsible for inducing autophagy with senescence selectively in cancer cells.